PERSEPSI SISWA TERHADAP PEMBELAJARAN SENI TARI DI KELAS XI IPS 2 SMA NEGERI 7 PADANG - Marde, Adinda Putri; Iriani, Zora (SENDRATASIK UNP, 2019)
AbstractÂ This research aims to see and describe the students perception toward dance learning in SMA Negeri 7 Padang. Type of the research was qualitative with using descriptive approach. The instrument in this study was the researcher and it was supported by using supporting instruments such as stationery and camera. Types of data used were primary and secondary data. Techniques of data collection were done by using observation, interview and library study. The steps in analyzing data were done by collecting, classifying, describing data and drawing conclusion. The result shows that in general the perception of students at SMA Negeri 7 Padang in class XI IPS 2 is not good. It is because the teachers should use more varied methods or techniques in dance learning, facilities and infrastructures should be provided by the school for dancing, students perception on the dance and perception improvement and students motivation to join the dance lesson that can be supported by inviting the students to pay more attention to dance learning as the subject as important as the other lessons.Keywords: Student perception, Dance Learning